GREEN PERFORMANCE AND EMPLOYEES’ CITIZENSHIP BEHAVIOR: EXAMINING THE ROLE OF EMPLOYEES’ PRIDE AND COMMITMENT - Anh Tuan PHAM; Truc Le NGUYEN; Xuan Trong HOANG; Hoang Phuong TRINH; Thi Van Anh LE; Van Anh VU; Trung Kien DANG; The Kien NGUYEN (Geo Journal of Tourism and Geosites, 2021)
Nowadays, employee behavior that has emerged as one of the most crucial factors that determine the success of organizations in general, and in tourism industry in particular. Previous researchers indicated that it is necessary to shed light on the mechanism influence of determinant factors on organizational citizenship behavior in the tourism industry. So that the main purpose of this study is to examine the mechanism of employees’ perceptions of green performance of hotels influence their organizational citizenship behavior (OCB) with the serial mediating effects of psychology (perceived pride) and emotion (affective commitment) of employees working in the hotel. A conceptual research model is developed and then empirically examined using PLS - SEM. The study data was collected from 209 employees working in hotel at Moc Chau national tourism area (Vietnam) via a questionnaire survey. The results show a positive correlation between employees’ perception of green performance of their hotel and their OCB. Interestingly, employees’ perceived pride and affective commitment act as serial mediators in the relationship correlation between employees’ perception of green performance of their hotel and their OCB. This study offers new insight for researchers and managers in the hospitality industry in term of ―go green‖ tendency.